(untitled) (Movimenta (ISSN 1984-4298), 2022)
Objective: To verify the caregivers’ perceptions about remote physiotherapy care in babies who are considered at risk whose ages range between zero and three years old, and to understand what were the barriers and facilitators experienced during this type of care. Materials and Methods: Qualitative research of the institutional case study type. Results: Eight caregivers were interviewed. Babies ranged from eight months of corrected age (CI) to two years and eleven months. In the sum of the economic questionnaire, the following classifications were obtained: B1, B2, C1 and C2. Regarding the level of education of the person who contributed the most to the household income, one completed elementary school, three completed high school and four completed higher education. On AHEMD-IS, only one home was rated excellent, presenting a wide range of variety and opportunities. Perceptions: privileged, satisfied and grateful even with difficulties, lack of knowledge and limitations. Increased parent-child connection and more time with the child, making it possible to get to know each other better. Barriers: lack of equipment/accessories, the environment was not prepared, lack of child collaboration and internet connection. Facilitators: continuous support from professionals, flexible schedules, adaptation to the family environment, not having to move around and the convenience of being at home. Conclusion: Telerehabilitation should be thought of as a viable post-pandemic option to ensure care and the sequence of care for patients, as it presented facilities for professionals and caregivers, and was able to include families in the intervention, allowing their participation in the treatment.